Predictors of Street Harassment Attitudes in British and Italian Men: Empathy and Social Dominance - Alessandra Giuliani; Daniel Campbell-Meiklejohn (Psychology International)
Background: Street harassment is a widespread issue affecting women’s freedom and well-being. While research has explored its impact on victims, little is known about individual factors influencing societal tolerance of such behaviour. This study examined the relationships of cognitive empathy and social dominance orientation (SDO) to street harassment tolerance among heterosexual men in two European cultures. Methods: A total of 136 Italian and 113 British heterosexual men completed measures of SDO and street harassment tolerance before and after watching a video depicting a woman experiencing harassment. Cognitive empathy was assessed through participants’ ability to recognise the victim’s emotional responses in the video. Results: Higher tolerances of street harassment before and after viewing the video were associated with lower cognitive empathy and higher SDO in both countries. Exposure to the video reduced street harassment tolerance in British participants but had no significant effect in the Italian sample. Conclusions: These findings highlight cognitive empathy and SDO as correlates of street harassment tolerance, suggesting their potential relevance for interventions to shift street harassment attitudes. The differing impact of the video between countries highlight the potential importance of cultural context for developing street harassment prevention strategies. Future research should further explore these relationships to inform targeted interventions.